2004
DOI: 10.4161/cc.3.11.1211
|View full text |Cite
|
Sign up to set email alerts
|

Brca1-Deficient Murine Mammary Epithelial Cells have Increased Sensitivity to CDDP and MMS

Abstract: Previously published online as a Cell Cycle E-publication: http://www.landesbioscience.com/journals/cc/abstract.php?id=1211 KEY WORDSBcra1-deficiency, DNA-damage and repair, breast cancer, CDDP, MMS ABBREVIATIONSMMECs murine mammary epithelial cells DAPI 4-6-diamidine-2-phenylidone dihydrochloride CDDP cis-platinum (II) diamine dichloride MTT 3-(4-5 dimethylthiozol-2-yl) 2-5diphenyl-tetrazolium bromide PBS phosphate-buffered saline MMS methylmethane sulfonate ACKNOWLEDGEMENTSWe like to thank Kevin Olson for te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 43 publications
(49 reference statements)
3
31
0
Order By: Relevance
“…Several in vitro studies show the relevance of the integrity of the BRCA1 pathway for tumor response to chemotherapy. It has been shown that BRCA1 deficiency is linked to sensitivity to cisplatin and other DNA damaging agents (44,45), although the need for further clinical studies of BRCA1 and response to chemotherapy has recently been highlighted (46). The current study is a retrospective study of a group of patients that have not all had the same chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Several in vitro studies show the relevance of the integrity of the BRCA1 pathway for tumor response to chemotherapy. It has been shown that BRCA1 deficiency is linked to sensitivity to cisplatin and other DNA damaging agents (44,45), although the need for further clinical studies of BRCA1 and response to chemotherapy has recently been highlighted (46). The current study is a retrospective study of a group of patients that have not all had the same chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of these BRCA1-defective models has suggested an increased sensitivity to specific categories of chemotherapeutic agents. In particular, BRCA1 deficiency seems to sensitize cells to alkylating agents that induce intrastrand and interstrand cross-links (ICL), phenomenon that has been associated to the role played by BRCA1 in homologous recombination (14,19), whereas contradictory results have been instead obtained with other chemotherapeutics such as the topoisomerase II inhibitors (15,16,19). The molecular bases of this characteristic response and how the increased susceptibility of BRCA1-defective tumor cells to ICL inducers may be exploited to improve the treatment of BRCA1 patients still require investigations.…”
Section: Introductionmentioning
confidence: 99%
“…Most of our knowledge on the role of BRCA1 in the drug response of breast cancer cells comes from studies done on murine cell models or on a breast cancer cell line (HCC1937) obtained from a carrier of BRCA1 mutation (14)(15)(16)(17)(18)(19). The analysis of these BRCA1-defective models has suggested an increased sensitivity to specific categories of chemotherapeutic agents.…”
Section: Introductionmentioning
confidence: 99%
“…BRCA1 defective cells show significant sensitivity to the DNA cross-linking agent mitomycin C, which is a hallmark of defective HR. 16,53 Indeed, HR defects confer sensitivity to a wide range of DNA cross linking agents. 54 HR can be measured directly using a plasmid based artificial DNA recombination substrate integrated into the genome.…”
Section: Introductionmentioning
confidence: 99%